2021
DOI: 10.5194/acp-21-2569-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Distinct emissions and volatility distribution of intermediate-volatility organic compounds from on-road Chinese gasoline vehicles: implication of high secondary organic aerosol formation potential

Abstract: Abstract. In the present work, we performed chassis dynamometer experiments to investigate the emissions and secondary organic aerosol (SOA) formation potential of intermediate-volatility organic compounds (IVOCs) from an on-road Chinese gasoline vehicle. High IVOC emission factors (EFs) and distinct volatility distribution were recognized. The IVOC EFs for the China V vehicle ranged from 12.1 to 226.3 mg per kilogram fuel, with a median value of 83.7 mg per kilogram fuel, which was higher than that from US ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 59 publications
8
43
2
Order By: Relevance
“…3 shows the EFs and compositions of the vehicular IVOCs in each retention-time based bin (Table S1). Similar to previous studies (Zhao et al, 2015(Zhao et al, , 2016Huang et al, 2018;Qi et al, 2019;Tang et al, 2021), the unspeciated cyclic compounds dominated the IVOCs, accounting for 59.07 ± 1.06%, followed by unspeciated b-alkanes (25.27 ± 0.75%) and speciated IVOCs (15.66 ± 0.60%). The speciated IVOCs consist of n-alkanes, b-alkanes and PAHs.…”
Section: Emission Factors and Compositions Of Ivocssupporting
confidence: 87%
See 4 more Smart Citations
“…3 shows the EFs and compositions of the vehicular IVOCs in each retention-time based bin (Table S1). Similar to previous studies (Zhao et al, 2015(Zhao et al, , 2016Huang et al, 2018;Qi et al, 2019;Tang et al, 2021), the unspeciated cyclic compounds dominated the IVOCs, accounting for 59.07 ± 1.06%, followed by unspeciated b-alkanes (25.27 ± 0.75%) and speciated IVOCs (15.66 ± 0.60%). The speciated IVOCs consist of n-alkanes, b-alkanes and PAHs.…”
Section: Emission Factors and Compositions Of Ivocssupporting
confidence: 87%
“…The distribution of IVOCs in retention-time based bins presented a significant decreasing trend with bin numbers. Previous studies have reported that more than 50% of IVOCs concentrated in higher-volatility bins like B12, B13 and B14 in gasoline exhaust while much broader volatility distributions were found in diesel exhaust (Zhao et al, 2015(Zhao et al, , 2016Tang et al, 2021). The IVOCs in B12 measured in this study was also the most abundant as the GVs previously tested in the US (Fig.…”
Section: Emission Factors and Compositions Of Ivocssupporting
confidence: 66%
See 3 more Smart Citations